New population of Solanum pimpinellifolium backcross inbred lines as a resource for heat stress tolerance in tomato - Bashary, Neta; Miller, Golan; Doitsch-Movshovits, Tzion; Beery, Avital; Ouyang, Bo; Lieberman-Lazarovich, Michal (Frontiers in Plant Science, 2024)
The occurring temperature increase in crop production areas worldwide is generating conditions of heat stress that negatively affect crop productivity. Tomato (Solanum lycopersicum), a major vegetable crop, is highly susceptible to elevated temperatures. Under such conditions, fruit set is dramatically reduced, leading to significant yield losses. Solanum pimpinellifolium, a wild species closely related to the cultivated tomato, was shown to have beneficial attributes under various abiotic stress growth conditions. We have utilized a new population of backcross inbred lines originated from a cross between S. pimpinellifolium and S. lycopersicum, in order to evaluate its potential as a new genetic resource for improvement of reproductive performance of cultivated tomato under heat stress conditions. This population was screened for various heat stress-related traits, under controlled heat stress and non-stress conditions. Our results show that significant variation exists for all the heat stress related traits that were examined and point at individual lines with better reproductive performance under heat stress conditions that share a common introgression from the wild S. pimpinellifolium parent, suggesting several candidate genes as potential drivers of thermotolerance. Thus, our results place this population as a valuable new resource for the discovery of heat stress related genetic loci for the future development of heat stress tolerant tomato cultivars.